Migration in the Central America of the Past. Reino of Guatemala, end of the Colonial Era - Castellón Osegueda, José Ricardo (2024)
Mobility is a phenomenon inherent in human history. Central America is experiencing one of the most acute migratory crises, yet studies on spatial and social mobility in its colonial past are scarce. This article is part of an ongoing research that aims to contribute to overcoming this reality. Using information obtained mainly from parish registers, the study focuses on five regions of the Reino of Guatemala between the eighteenth and nineteenth centuries, in order to reveal the migratory phenomenon inserted in the intense social and geographical mobility that characterized the region at that time. The results show that social and geographic mobility are key factors in Central American history and indispensable for understanding its social reality.